Islamist terrorism and the role of women - Daniel Meierrieks; Laura Renner (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2021)
We investigate the effect of Islamist terrorist activity on women's economic, political and legal position in society, using data for 168 countries between 1970 and 2016. We provide robust evidence that increased activity by Islamist terrorist groups is associated with lower levels of women's empowerment and rights. Various instrumental-variable approaches yield the same conclusion, suggesting that the adverse effect of Islamist terrorism on women' rights is causal. Further emphasizing the role of violent Islamist fundamentalism, we find no evidence that Islam per se (as indicated by a country's Muslim population share) affects the position of women in society. Finally, we show that left-wing and nationalist-separatist terrorism do not affect women's rights, which reinforces the notion that Islamist terrorism is singularly interested and effective in achieving weaker women's rights. We argue that our findings are consistent with predictions of a strategic model of terrorism, where (1) Islamist terrorists use violence to curb women's rights because they consider modern notions of gender equality to be corruptive and (2) governments make concessions that constrain the role of women in society because the costs of compliance are lower than the political and economic harm that would result from further Islamist terrorist attacks.
Keywords: D74; H11; K00; 330; Islamist terrorism; women's rights; gender equality; effectiveness of terrorism; strategic model of terrorism